Q: Factor x2 - 10x plus 1?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

(x+1)(x+9)

x2+10x+1 = -12+2x x2+10x-2x+1+12 = 0 x2+8x+13 = 0 Solving by using the quadratic equation formula: x = - 4 - or + the square root of 3

x2+10x+1 = -12+2x x2+8x+13 = 0 The solution: x = -4 + the square root of 3 or x = -4 - the square root of 3

x2 - 10x - 6 = 2x + 1 Subtracting 2x + 1 from both sides gives: x2 - 12x - 7 = 0

x2 + 2y - 6x + 8y - 1 = x2 - y2 + 4x + 6y - 1 y2 - 10x + 4y = 0 y(y+4) = 10x It cannot be solved completely because with two variables (x and y) you need two independent equations for a full solution.

Related questions

(x+1)(x+9)

(x+1)(x+9)

x2 + 9 = 10x x2 - 10x + 9 = 0. (x - 9)(x - 1) = 0. Therefore, x = 1 or 9.

x2+10x+1 = -12+2x x2+10x-2x+1+12 = 0 x2+8x+13 = 0 Solving by using the quadratic equation formula: x = - 4 - or + the square root of 3

x2+10x+1 = -12+2x x2+8x+13 = 0 The solution: x = -4 + the square root of 3 or x = -4 - the square root of 3

x2 - 10x - 6 = 2x + 1 Subtracting 2x + 1 from both sides gives: x2 - 12x - 7 = 0

x2(x3 + 1) is the best you can do there.

You can't factor it

1

3x2 + 10x + 3 = (x + 3)(3x + 1).

4x(10x + 1)

x3 + x2 + 4x + 4 = (x2 + 4)(x + 1)